Case Comment: Greenmail, Japanese Style - Milhaupt, Curtis J. (Columbia Journal of Asian Law, 2012)
This comment analyzes the Janome Sewing Machine case, a high profile 2006 judgment of the Supreme Court of Japan on the personal liability of corporate directors for engaging in an elaborate scheme to repurchase company shares held by an undesirable shareholder with links to organized crime. The litigation offers insight into a rather dark period in Japanese corporate history and provides a platform for considering larger questions about Japan’s institutional incentive structures and law enforcement climate. While the conduct at issue in the case, typically known as “greenmail,” seems to have abated in Japan, critics may argue that it has been replaced by its white collar equivalent-short-term oriented private equity and hedge fund activism. Thus, the comment concludes with a reference to a more recent, controversial decision of the Japanese Supreme Court, Bull-Dog Sauce, endorsing as a valid defensive measure target management’s large-scale payoff to a Wall Street investment fund to thwart its tender offer for the firm.